P PENDIDIKAN ANDRAGOGI DALAM MEMBENTUK ANAK SUPUTRA MELALUI AJARAN TRI KAYA PARISUDHA - Ni Kadek Ayu Pradnyanita (Jurnal Pendidikan Agama, 2022)
Education has a very large role in the development and improvement of the quality of self and behavior of community and state life. Through the process of education the child will be able to develop all the potential that exists in him, both in the realm of knowledge, attitudes, behavior and skills. One sign that a person has learned is a change in behavior in him, changes in behavior that are knowledgeable (cognitive), skills (psychomotor) and related to values and attitudes (affective). Guidance from adults as an educator is indispensable by a child in shaping personality, emotional, attitude, behavior, and skill development in this case is often called andragogy education. Andragogy education is a way of shaping humans in shaping one's personality, or adult guidance in providing education to children to acquire a good personality. In Hinduism, forming a good personality has guidelines that must be owned by every child, namely the teachings of tri kaya Parisudha. Andragogy education is used in educational units both informal education and formal education, of course in this case through andragogical education combined with the concept of Tri Kaya Parisudha teachings will have an influence on children's behavior.